Torsional malalignment, how much significant in the trochanteric fractures?. Issue 11 (November 2015) - Kim, Tae Young; Lee, Yong Beom; Chang, Jun Dong; Lee, Sang Soo; Yoo, Jae Hyun; Chung, Kook Jin; Hwang, Ji Hyo
Abstract: Objectives: The rotational alignment is definitely important in the long bones such as tibias and femurs. We also predict the importance of rotational alignment in the trochanteric fractures. So we measured torsional malalignment in trochanteric fracture and anlaysed their risk factors and their clinical significance. Methods: A total of 109 inpatients who had undergone internal fixation following trochanteric fracture and a postoperative pelvic CT scan between 2008 and 2013, with at least one year follow-up, were selected. Factors that affect torsional malalignment, such as age, gender, fracture stability, injured area, operative time, time of surgery after admission, and ASA status, were investigated. Factors that affect the patients' clinical results in malrotation, including ambulation time after surgery, postoperative complication rates, pain assessment of VAS one year postoperatively and Koval score, were also investigated. Results: Of the 109 subjects, torsional malalignment was observed in 28 (25.7%) subjects with a mean torsional malalignment angle of 20.7° (range: −31.2° to 27.1°). Torsional malalignment risk factors were fracture stability ( p = 0.021) and operative time ( p = 0.043). In terms of the time to ambulation after surgery, the postoperative complication rates, and the VAS and Koval scores at one year postoperatively, no statistically significant difference was observed between the torsional malalignment patients and the non-deformity patients. Conclusions: In this study, 25.7% of the patients who had undergone internal fixation following trochanteric fracture experienced torsional malalignment. Major factors of the torsional malalignment were an unstable fracture and the consequent delay in the operative time. But the torsional malalignment was deemed to have no effect on clinical results.